KOORDINASI PEMERINTAH DAERAH, SWASTA DAN MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA PANTAI SELATBARU DI KABUPATEN BENGKALIS TAHUN 2018-2019 - M. Ubaidi; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In the era of regional autonomy, regional governments have the authority to develop the potentials of their regions according to their respective characteristics. This includes concurrent government affairs, namely government affairs that are divided between the Central Government and the provincial and district/city regions. One of the potentials that can be developed in an area is the tourism sector. Coordination in the development of Selatbaru beach tourism objects is carried out by the Regional Government, namely the Bengkalis Regency Tourism, Culture, Youth and Sports Office, Traders (Private), and the Community. This research is motivated by the lack of clarity in the direction of coordination among the actors involved in the development of the Selatbaru beach tourism object, as well as the unclear existence and function of tourism institutions in the Selatbaru beach tourism object environment. Thus, the physical and non-physical management and development program for the Selatbaru beach tourism object did not run well, especially in 2018-2019.The approach in this research uses a qualitative approach. This type of research is descriptive research. The research location is on Selatbaru Beach, which is located in Selatbaru Village, Bantan District, Regency. Bengkalis. The types of data used in this study are primary data and secondary data. Data collection techniques were carried out through interviews, and documentation. The data analysis technique in this research is qualitative data analysis.The results of the study show that the coordination of the local government, the private sector and the community in the development of the Selatbaru beach tourism object in Bengkalis Regency in 2018-2019 has not gone well. The existing institutions or organizations in the development of Selatbaru beach tourism objects are still unclear and not well structured. This causes the early stages or the policy planning process to run slowly, due to the lack of data that should be obtained from institutions or organizations around the Selatbaru beach tourism object. communication between actors is still relatively minimal which is usually done only during meetings and socialization meetings, and information related to meeting procurement often does not reach the wider community. The factors that hinder the synergy of actors are the low level of human resources, the lack of communication between the actors, and the lack of a budget that is directed to the tourism sector. Keywords: Coordination, Development, Tourism